Oxygen uptake kinetics as a determinant of sports performance - Burnley, M.; Jones, A. M. (European Journal of Sport Science, 2007)
It is well known that physiological variables such as maximal oxygen uptake (VO2max), exercise economy, the lactate threshold, and critical power are highly correlated with endurance exercise performance. In this review, we explore the basis for these relationships by explaining the influence of these "traditional" variables on the dynamic profiles of the VO2 response to exercise of different intensities, and how these differences in VO2 dynamics are related to exercise tolerance and fatigue. The existence of a "slow component" of VO2 during exercise above the lactate threshold reduces exercise efficiency and mandates a greater consumption of endogenous fuel stores (chiefly muscle glycogen) for muscle respiration. For higher exercise intensities (above critical power), steady states in blood acid-base status and pulmonary gas exchange are not attainable and VO2 will increase with time until VO2max is reached. Here, we show that it is the interaction of the VO2 slow component, VO2max, and the "anaerobic capacity" that determines the exercise tolerance. Essentially, we take the view that an appreciation of the various exercise intensity "domains" and their characteristic effects on VO2 dynamics can be helpful in improving our understanding of the determinants of exercise tolerance and the limitations to endurance sports performance. The reciprocal effects of interventions such as training, prior exercise, and manipulations of muscle oxygen availability on aspects of VO2 kinetics and exercise tolerance are consistent with this view.